Synthesis, Characterization And Theoretical Studies On A New Donor-pi-acceptor (D-π-a) Bridge System Of Ferrocenyl Chalcones For Potential Solar Cell Applications - Anizaim, Ainizatul Husna (2021)
15 organometallic compounds known as ferrocenyl chalcones were designed for application in dye-sensitized solar cell (DSSC) based on a donor-π-acceptor (D-π-A) architecture. The compounds were strategically synthesized using Claisen-Schmidt condensation method by introducing different substituents and successfully yielded 5 single crystals of ferrocenyl chalcones. All synthesized compounds were further characterized using IR and NMR methods. The UV-Vis spectroscopic study revealed the spectrum for all ferrocenyl chalcones are bathrochromically shifted up to 500 nm which are suitable for DSSCs application. Target compounds were further investigated by X-ray analysis and studied computationally using Density Functional Theory (DFT) approach to explore the potential in DSSCs. Different substituents in five ferrocenyl chalcone single crystals have been proven in enhancing intramolecular charge transfer (ICT) by improving the planarity of the compounds’ backbone. The crystal packings show the head-to-tail and side by side arrangements via intermolecular C–H···O, C–H···F, C–H···π and π···π interactions. The molecular electrostatic potential (MEP) illustrates the strength of the push-pull system by the positive, negative, and neutral electrostatic potential sites of all compounds